Interference relationships between weeds and sugarcane in the ‘plene’ system - Mossin, C. B. [UNESP]; Hijano, N. [UNESP]; Nepomuceno, M. P. [UNESP]; Carvalho, L. B. [UNESP]; Alves, P. L.C.A. [UNESP] (FapUNIFESP (SciELO), 2019)
Sugarcane is one of the most important crops planted in Brazil in that the presence of weeds in the fields has promoted significant yield reduction. The objective of this work was to evaluate the differential growth response of two sugarcane varieties cropped in the ‘Plene’ system as a function of the coexistence with different weed species. Treatments consisted of the coexistence of Bidens pilosa plus Ipomoea quamoclit, Ipomoea hederifolia, Amaranthus viridis, Urochloa plantaginea, Panicum maximum, and Digitaria horizontalis with two sugarcane varieties (RB92579 and SP80-1842) cropped in the ‘Plene’ system, in addition to a control without weeds. The design was completely randomized with three replicates. Dry matter accumulation of weeds was dependent of the weed species and the sugarcane variety whose coexistence was kept. The behavior of development in terms of plant height, number of green leaves, leaf area, and dry mass of stems, roots and leaves was dependent on the sugarcane variety and on the weed species whose coexistence was kept. The weed U. plantaginea showed the greatest potential to interfere with the growth of both sugarcane varieties planted in the ‘Plene’ system. Panicum maximum and D. horizontalis are also potential competitors, while B. pilosa, I. quamoclit, I. hederifolia, and A. viridis are less competitive. The sugarcane variety RB92579 is less susceptible to weed interference than SP80-1842 when planted in the ‘Plene’ system.
Relações de Interferência de Plantas Daninhas com Cana-de-Açúcar no Sistema ‘Plene’
Keywords: Guinea grass; Jamaican crabgrass; Marmalade grass; Morning glory; Saccharum officinarum; Slender amaranth